AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN TALAS KETAN (Colocasia esculenta) TERHADAP BAKTERI Saphylococcus aureus DAN Salmonella thypi SECARA DIFUSI AGAR - Herwin Herwin; Muzakkir Baits; Ririn Ririn (Fakultas Farmasi UMI, 2016)
Antibacterial activity of taro leaves ekxtract has been conducted. The Recearch aimed to determine the antibacterial activity and concentration of ethanol extract of taro leaves (Colocacia esculeta) inhibited the growth of either Salmonella thypi and Staphylococcus aureus by agar diffusion. The result of the antibacterial activity screening in concentration of 1% showed that the ethanol extract of taro leaves by solid dilution provided activity againts Salmonella thypii and Staphylococcus aureus. Based on the test results of antibacterial activity by agar diffusion using concentration of 1% , 2% and 4 % showed that the ethanol extract of taro has the largest inhibition zone diameter againts Staphylococcus aureus of 4% was 15 mm.